Design and testing of fluid resistor for repetitive high-voltage pulse generator; Energy Fluxes and Radiation Effects (EFRE-2016) - Egorov I. S. Ivan Sergeevich; Poloskov A. V. Artem Viktorovich; Ezhov V. V. Vitali Vladimirovich; Serebrennikov M. Maksim (2016, 2016)
Title screen